THE ROLE OF WOMEN IN REALIST FICTION - Eldorbek Erkin og’li Khamitov,; Markabaeva Mexriban Keulimjayevna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This study focuses on the role of women in realist fiction and explains how female characters are used to present real life and social reality. In realist literature, women often become central figures because their daily experiences clearly show the problems existing in society. Unlike romantic or ideal characters, women in realist works are portrayed as realistic individuals with ordinary lives, responsibilities, and difficulties. Female characters in realist fiction belong to various social backgrounds and perform different roles, such as mothers, wives, daughters, and workers. Through these roles, authors demonstrate how social rules and traditions influence women’s lives and limit their freedom. At the same time, realist writers give much attention to women’s inner world, showing their emotions, thoughts, and personal struggles. These characters help reveal social injustice, inequality between men and women, and moral challenges. Moreover, women’s lives in realist fiction often reflect wider social issues. Their personal  stories  are  connected  with  problems  such  as  economic  hardship,  forced marriage,  lack  of  rights,  and  limited  access  to  education.  Some  realist  works  also present  women  as  strong  personalities  who  try  to  change  their  situation  and  seek independence despite social pressure. To sum up, women play an essential role in realist fiction because they help portray  society  in  a  truthful  and  realistic  way.  Through  female  characters,  authors express  criticism  of  social  systems  and  raise  important  questions  about  justice, morality,  and  the  status  of  women.  Therefore,  the  depiction  of  women  remains  a significant element of realist literature.